Design of a rainwater harvesting system for the Institute of Civil Engineering Main Building towards the development of a framework for academic buildings in UP Diliman - Amolato, Rochie D.; Lumbera, Maxell P. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
As water demand increases in Metro Manila and water supply infrastructures are least likely to be built for the next years, there will come a time where the demand of the population for water will exceed the available supply from centralized water line systems. Thus, there is a need for an alternative water supply. A rainwater harvesting (RWH) system, made of a catchment area, conveyance, and storage, is proven to be potentially viable for a number of applications. Quezon City Building Ordinance mandates new buildings to incorporate water use reduction strategies, particularly an RWH system. In this study a RWH system is to be designed, the case of the University of the Philippines Diliman Institute of Civil Engineering Main Building is considered representing a number of academic buildings in the campus. Calculations were made to obtain the reliability curve, system schedule, and layout options as basis for recommending the applicable system for the building. With a budget of one million a 30,000 L elevated steel storage tank is chosen. It is to be placed at the left front side of the building. This storage is suggested to augment the water supply and serve 75% of the demand with 45% reliability. A schedule has also been developed to further increase the reliability to 60%. From the calculations, a summary of the procedures was made as an initial step in developing a framework that will guide building owners, designers, and/or contractors to incorporate RWH in the building design. This study mainly involves academic buildings, consideration of other buildings would help create a more generalized framework.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: University of the Philippines. -- College of Engineering. -- Institute of Civil Engineering; Water harvesting; College buildings -- Philippines